Fabrication laboratories The development of new business models with new digital technologies - Santos, Gilberto (2018)
Purpose – The purpose of this paper is to analyze the current state of fabrication laboratories (Fab Lab), an international network of digital laboratories, which provides new technological tools for digital manufacturing that can be used from individual users, to small businesses and schools. The aim is to understand similarities and differences of skills, technologies used and customers served among the main European laboratories (Italy, France, Germany, the Netherlands and Spain) and the American ones. Design/methodology/approach – Data from European and American Fab Labs were collected using a questionnaire survey performed on a total sample of n¼493 Fab Labs. The administration of the survey took place through e-mail; 73 Fab Labs participated to the survey, reaching a total response rate of 14.81 percent. Findings – The results show that Italian laboratories are characterized by ample space available, but limited capacity for investment in machinery and technology. European Fab Labs are similar to the Italian Fab Labs, while the American ones are more heterogeneous in size. However, a fact that emerges clearly from the results is how American Fab Labs are more important realities than European ones in terms of turnover and investments. They are more similar to businesses with an independent financial support. Originality/value – The novelty of the study resides in the issue considered and the experimental techniques used. Some qualitative case studies have been developed in the field, but no previous quantitative analyses have been developed on a large sample of Fab Labs, developing comparisons between European and American realities of these digital laboratories.